Estudo retrospectivo de 19 casos de polioencefalomalácia, em bovinos, responsivos ao tratamento com tiamina Retrospective study of 19 cases of polioencephalomalacia in cattle, responsive to the treatment with thiamine - L.C.N. Mendes; A.S. Borges; J.R. Peiró; F.L.F. Feitosa; C.R. Anhesini (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2007)
Nineteen bovines of both sexes aging from 5 month-old to 5 year-old, were referred to a veterinary hospital. Clinical signs were observed from 6 hours to 10 days before. Thirteen animals were found in permanent lateral recumbency, five showed motor incoordination, 15 were exclusively fed on grass pasture, three showed partial loss of visual acuity, 14 were blindness, 16 showed presence of normal pupillary reflex, 16 decreased ruminal motility, 14 decreased sensorium (depression, semicoma or coma) and eight showed opisthotonos. Dehydration and dried feces were directly related to the time of evolution of the process. All the animals were administrated vitamin B1 and showed a marked improvement of the clinical status within 4 to 48 hours after treatment. The longer the time between the onset of the clinical signs and treatment, the greater the delay for the restoration of the vision. The treatment was very effective for a rapid response of the animal.